2012
DOI: 10.1186/1756-0500-5-441
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward depression among Japanese non-psychiatric medical doctors: a cross-sectional study

Abstract: BackgroundUnder-recognition of depression is common in many countries. Education of medical staff, focusing on their attitudes towards depression, may be necessary to change their behavior and enhance recognition of depression. Several studies have previously reported on attitudes toward depression among general physicians. However, little is known about attitudes of non-psychiatric doctors in Japan. In the present study, we surveyed non-psychiatric doctors’ attitude toward depression.MethodsThe inclusion crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 10 publications
(13 reference statements)
3
31
0
Order By: Relevance
“…There appeared to be considerably less misinformation and stigma about depression in this sample compared to a previous study of Indian non-psychiatric clinicians 20 , which suggests that HIV providers may have been sensitized to the importance of behavioral health. Encouragingly, compared to non-psychiatric clinicians in high-income countries 24,27 , including HIV clinicians in the United States 23 , the Indian HIV providers sampled in our study appeared to endorse to a similar (if not greater) extent favorable attitudes toward PLHIV and a willingness to diagnose and treat depression. We found that these opinions and attitudes were generally held regardless of respondents’ gender, rural vs. urban practice locale, employment in public or private practice, years in practice, or numbers of PLHIV seen per month.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…There appeared to be considerably less misinformation and stigma about depression in this sample compared to a previous study of Indian non-psychiatric clinicians 20 , which suggests that HIV providers may have been sensitized to the importance of behavioral health. Encouragingly, compared to non-psychiatric clinicians in high-income countries 24,27 , including HIV clinicians in the United States 23 , the Indian HIV providers sampled in our study appeared to endorse to a similar (if not greater) extent favorable attitudes toward PLHIV and a willingness to diagnose and treat depression. We found that these opinions and attitudes were generally held regardless of respondents’ gender, rural vs. urban practice locale, employment in public or private practice, years in practice, or numbers of PLHIV seen per month.…”
Section: Discussionmentioning
confidence: 58%
“…These 29 items, which were grouped into five categories, asked respondents to agree with statements about depression in PLHIV using a 5-point Likert scale (strongly agree, agree, neutral, disagree, strongly disagree). The questionnaire was adapted from other published questionnaires on provider attitudes toward mental health 23,24 , including two from India 25,26 . Study materials were written in English, which was the primary language used at CART 2015.…”
Section: Methodsmentioning
confidence: 99%
“…The finding is compatible with a notion that nonpsychiatrists are reluctant to manage patients with depression (Ohtsuki et al, 2010), and they tend to think that treatment of depression is reserved to only psychiatrists (Ohtsuki et al, 2012). Furthermore, they indicated to judge the efficacy of antidepressants in 8.6 days after prescribing them, which is rather hasty in light of the recommended duration of 2-4 weeks in the guidelines (NICE, 2009).…”
supporting
confidence: 59%
“…In Japan, it has been reported that only 7.4% of patients with depression received optimal treatment in a general hospital (Ohtsuki et al, 2010) despite at least equivalent prevalence of depression in medical inpatients compared to those in other countries (21.5% vs. 5.0-21.0%) (Forkmann et al, 2011;Hosaka et al, 1999;Silverstone et al, 1996). This condition may be, at least to some extent, attributable to lack of confidence, recognition, and motivation towards depressive care among non-psychiatrists (Ohtsuki et al, 2010(Ohtsuki et al, , 2012. Moreover, such non-psychiatrists' negative attitude on depression may result in insufficient utility of consultation-liaison psychiatry; however, the attitude on depression among non-psychiatrists in general hospitals remains unclear.…”
mentioning
confidence: 92%
“…Knowledge among GPs of mental disorders may vary from country to country and depends on the amount and quality of training received both at under‐ and postgraduate levels (James, Jenkins, Lawani, & Omoaregba, ). Developing a focused medical educational program that motivates GPs to play a role in depression care is necessary to enhance recognition and treatment of depression, as suggested, for example, by studies in Japan (Ohtsuki et al, ), France (Mercier et al, ), and Australia (Richards et al, ). However, participation in mental health training by GPs appears to be related to their attitudes towards depressed patients and to their confidence and abilities to diagnose and manage common mental disorders effectively (Williams et al, ).…”
Section: Discussionmentioning
confidence: 99%